UPAYA MENINGKATKAN MINAT BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING PADA MATA DIKLAT KOMUNIKASI SISWA SMK - Pratiwi, Dian; Marimin, Marimin (Economic Education Analysis Journal, 2016)
Tujuan penelitian untuk meningkatkan minat belajar siswa melalui model pembelajaran kooperatif tipe Snowball Throwing pada mata diklat komunikasi siswa kelas X AP SMK Gatra Praja Pekalongan. Subjek penelitian ini adalah siswa kelas X AP yang berjumlah 37 siswa. jenis penelitian adalah penelitian tindakan kelas, dilakukan dalam dua siklus. Teknik pengumpulan data menggunakan observasi, kuesioner,dan dokumentasi. Hasil penelitian menunjukkan minat belajar hasil dari lembar pengamatan siklus I sebesar 60,33% dengan kategori kurang berminat dan pada siklus II menjadi 75,27% dengan kategori berminat. Sedangkan hasil minat belajar dari angket/kuesioner pada siklus I 68,90% dengan kategori berminat dan pada siklus II menjadi 76,71% dengan kategori berminat. Kesimpulanya Penerapan pembelajaran menggunakan model Snowball Throwing dapat meningkatkan minat belajar siswa kelas X AP pada mata diklat komunikasi SMK Gatra Praja Pekalongan, terbukti setiap siklusnya mengalami peningkatan.This study is aimed at improving students’ interest through cooperative learning model Snowball Throwing at Communication Training Subject in Class X Office Administration of Gatra Praja Vocational High School Pekalongan. Subject of this research was the 37 students of XI AP. This type of research is classroom action research and conducted in two cycles. Data collecting technique used is observation, questionnaires, and documentation. The result of the research shows that the learning interest form of the observation sheet on the first cycle is 60.33% with less interest category and the second cycle, it turns into 75.27% to the category of interest. While the results of the learning interest from the questionnaire in the first cycle is 68.90% of the maximum percentage of the interest category and the second cycle it turns into 76.71% to the category of interest. The conclusion is the application of learning using models Snowball Throwing can increase students’ interest in the class X Office Administration on communication training subject in Gatra Praja Vocational High School Pekalongan, it is proved from the implementation of the method which improves students’ achievement on each cycle.